Media Kultur Alternatif In Vitro Pada Nematoda Entomopatogen: Alternative In Vitro Culture Media for Entomopathogenic Nematodes - Iqbal Erdiansyah; Rio Yudha Pratama; Trisnani Alif; Tirto Wahyu Widodo (Gontor Agrotech Science Journal, 2024)
Entomopathogenic nematodes (ENPs) are prospective biological agents. The obstacles multiplication of NEP are limited access to purchasing and the high price of multiplication media. This research aims to determine effect of alternative media composition on the population density of Entomopathogenic Nematodes. This research was conducted in August-December 2022 using a completely randomized Design (CRD) with 7 treatments, its MA (4g rice bran), MB (4g coconut pulp), MC (4 g golden snail), MD (2 g rice bran + 2 g coconut pulp), ME (2 g rice bran + 2 g golden snail), MF (2 g coconut pulp + 2 g golden snail), MG (2 g rice bran + 1 g coconut pulp + 1 gram golden snail) was repeated 4 times. The observed variable is densitiy of Nematodes Population. The data obtained were analyzed using ANOVA and continued with the 5% Tukey test. The results showed a significant effect of alternative medium on the NEP population with the best treatment on MG medium, the average population in 1st week (1044.25J/0.25ml), 2st week (1120.75J/0.25ml), 3st week (177J/0.25ml) and 4st week (89.25J/0.25ml)